Structural development and bioactive content of red bulb plant (Eleutherine americana); a traditional medicines for local Kalimantan people - EVI MINTOWATI KUNTORINI; LAURENTIUS HARTANTO NUGROHO (Society for Indonesian Biodiversity, 2010)
Kuntorini EM, Nugroho LH (2010) Structural development and bioactive content of red bulb plant (Eleutherine americana); atraditional medicines for local Kalimantan people. Biodiversitas 11 (2): 102-106. Red bulb plant or â€œbawang dayakâ€ (Eleutherine americana Merr.) is commonly used as a traditional medicine especially for anti breast cancer of Kalimantan people, because it contains bioactive naphtoquinone-derivatives. Naphtoquinones is usually used as antimicrobial, antifungal, antiviral and antiparasitic agents. This study was aimed to complete the investigation of Red bulb plant as a traditional medicine from anatomical and phytochemical point of view, especially the anatomical structure of bulb and leaf of red bulb plants during their development and their naphtoquinone derivative contents. The anatomical structures of bulb and leaf were analyzed by paraffin embedding method and naphtoquinone derivative contents were analyzed using HPLC. During plant development, the diameter and the length of bulbs as well as the thickness of mesophyll and epidermis layers of the leaves increased significantly. The size of vascular bundles increased and so did phloem and xylem components. The content of bioactive compounds in bulbs increased significantly as the size of parenchymal cells increased. There was no significant difference in the content of bioactive compounds of leaves during development, despite the rise in the thicknessof mesophyll and the constituting cells as the location of synthesis.Key words: development, bulb, leaf, Eleutherine americana, naphtoquinone